An examination of ground reaction forces of three pole vault take-off styles - Christensen, B.; Francis, S.; Keller, S.; Strand, B.; Hatterman-Valenti, H. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this study was to compare ground reaction forces of pole vault take-offs when the take-off foot is out, on, and under the top hand hold position. The take-off is regarded as the most important phase of the pole vault yet there is an insufficient amount of research on the ground reaction forces of the pole vault take-off. At this time there is not any scientific research comparing ground reaction forces between take-offs that are out, on and under the top hand hold. A total of 108 jumps with a take-off from a force plate were used for analyses. The jumps were put into categories of out, on and under and analyzed by Accupower and Dartfish software. Separate mixed modal ANOVAs were applied (p<.05) for comparison between jump types. No significant differences were found in ground reaction forces between the three take-off types.